Pengaruh Profesionalisme, Independensi, Komitmen Organisasi, Dan Spiritual Intelligence Terhadap Kinerja Auditor Dimasa Pandemi Covid-19 - Vita Andiana Sari (Jurnal Ilmiah Sultan Agung, 2022)
This study aims to determine the effect of professionalism, independence, organizationalcommitment, and spiritual intelligence on auditor performance during the COVID-19 pandemicat the Semarang City Public Accounting Firm (KAP) registered in the Information System of thePublic Accountant Office of the Supreme Audit Agency (SIKAP BPK). This study uses aconvenience sampling technique (availability of respondents). Based on the results of thequestionnaire distribution, 48 respondents were obtained from 15 Public Accounting Firms(KAP) in the city of Semarang. Then the analytical technique used is multiple linear regressionanalysis which is processed using SPSS 16. Based on the results of the tests that have been carriedout, this study shows that professionalism, independence, and organizational commitment have apositive and significant effect on auditor performance during the covid-19 pandemic. Meanwhile,spiritual intelligence has no significant effect on auditor performance during the COVID-19pandemic.Keywords: Professionalism, Independence, Organizational Commitment, Spiritual Intelligence,Auditor Performance